2013
DOI: 10.1111/jscm.12011
|View full text |Cite
|
Sign up to set email alerts
|

Power Asymmetry, Adaptation and Collaboration in Dyadic Relationships Involving a Powerful Partner

Abstract: Buyer–supplier relationships involve dyadic interactions, but there is a dearth of empirical dyadic analysis of these relationships. While relationships with a power balance between partners do exist, relationships typically occur in the context of power asymmetry. This study examines how perceptions of power use and prevailing relationship quality in dyadic relationships characterized by substantial power asymmetry affect behavioral and operational outcomes. Hierarchical regression is used to analyze data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
409
3
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(452 citation statements)
references
References 103 publications
(180 reference statements)
30
409
3
10
Order By: Relevance
“…In contrast to process-based socially responsible procurement practices, when mediated power is used to achieve innovative or strategic practices, researchers consistently find a negative effect. For example, in the power literature, Nyaga et al (2013) find that mediated power use negatively affects both collaborative behavior and the supplier's willingness to adapt products or processes to suit the buyer. Benton and Maloni (2005) find that coercive buyer power has a detrimental impact on relationships in the automotive industry and Jones and Pollitt (1998) suggest that opportunistic or abusive use of power leads to not only a reduction in the quality of products but also a parallel lack of investment and innovation by suppliers.…”
Section: Hypothesis 1amentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to process-based socially responsible procurement practices, when mediated power is used to achieve innovative or strategic practices, researchers consistently find a negative effect. For example, in the power literature, Nyaga et al (2013) find that mediated power use negatively affects both collaborative behavior and the supplier's willingness to adapt products or processes to suit the buyer. Benton and Maloni (2005) find that coercive buyer power has a detrimental impact on relationships in the automotive industry and Jones and Pollitt (1998) suggest that opportunistic or abusive use of power leads to not only a reduction in the quality of products but also a parallel lack of investment and innovation by suppliers.…”
Section: Hypothesis 1amentioning
confidence: 99%
“…Supply chain researchers have concluded that power is antecedent to the supplier's willingness to make adaptations for its buyers (Nyaga et al 2013), with research showing that non-mediated power use has a positive impact on relationships (Benton and Maloni 2005;Zhao et al 2008).…”
Section: Power Use and Socially Responsible Procurement Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…It analyses the relationship that develops in an economic exchange when an individual (the principal) concedes authority to another (the agent) to act in his or her name (Cuevas-Rodríguez, Gomez-Mejia, & Wiseman, 2012). The exercise of coercive and legal power has a strong negative effect on collaborative behaviour, while rewards have a positive effect (Nyaga, Lynch, Marshall, & Ambrose, 2013). The central goal of agency theory is to stop opportunistic behaviour in a situation where parties have different goals and the information supply is incomplete (i.e.…”
Section: Problem Definitionmentioning
confidence: 99%